Development and Evaluation of Injectable in Situ Implant for Sustained Release of Meloxicam Based on Biodegradable Polymers (Musk and Mastic) - Otaq, Mahfood Omer; Othman, Gamil Qasem; Al-Tahami, Khaled Abdullah (World Journal of Pharmaceutical Research, 2020)
The main objective of this study was to develop and to evaluate meloxicam in situ implant from biodegradable polymeric substances to attain sustained release of meloxicam, which help to manage pain for long time and reduce side effect. Methods: meloxicam in situ implant or precipitate was prepared by phase separation method employing musk and mastic as biocompatible and biodegradable polymers in several concentrations of polymers and solvent. The formulated meloxicam implant / precipitate were evaluated for implant / precipitate morphology, viscosity of solution or suspension and syringability, drug entrapment efficiency, loading of drug, drug-polymer combination compatibility, the drug release in- vitro study and accelerated stability study. Results: The proportion entrapment efficiency of drug was existing within the acceptable limit and found to be higher in case of mixed biodegradable polymer (Musk, Mastic) with xanthan gum as compared to low concentration of musk alone. From Fourier transform infra-red spectrums of the implant or precipitate observed no interference between meloxicam with the polymers applied. Scanning electron microscope examined of implant observed small coarse spherical or gel precipitate. The release in vitro study of meloxicam from the all formulations was different polymers with different concentration. Long meloxicam release was showed in formulation has musk concentration or mixed two polymers with medium viscosity after injected in phosphate buffer media at PH 7.4 throughout eight days. The proportion of entrapment efficiency and loading of drug elevated whereas meloxicam sustained release from polymeric implant or precipitate, when the drug used with different types and concentration of polymer ratio increased. The initial burst release was acceptable in most formulation and showed acceptable stability of best formula exactly in F12 with good correlation coefficients R2. Conclusion: The results which it obtained from this study the Meloxicam, implant / precipitate from biodegradable polymers were performed to be appropriated delivery of meloxicam or any active drugs as safe and efficient sustained delivery system.